The Effect of a Face-To-Face ScienceReady Preparatory Short Course on University Students' Self-Efficacy. - Thalluri, Jyothi; Penman, Joy; Chau, Minh (Student Success v.12 n.1 p.72-81 https://doi.org/10.5204/ssj.1698, 2021)
The ScienceReady preparatory course is an intensive study designed to improve beginning university undergraduate students' understanding of medical/scientific concepts, and reduce their anxiety about studying the science component of their enrolled programs. Its goals are to stimulate students' science curiosity and provide the fundamental scientific content they are expected to know and build further on the knowledge that will feature in their upcoming programs. This article aims to describe the ScienceReady course, discuss the impact of the course on the participants, determine the relationship of the course with self-efficacy, and explain the implications of the results. Students were tested before and after the course to ascertain whether it increased or decreased or not affected self-efficacy. The results of the pre- and post-test surveys were unequivocal. The majority of the individual items for the self-efficacy questionnaire showed a significant increase in self-efficacy post-course. [Author abstract]